Persinggungan Filsafat dengan Bahasa Arab - Teguh Hadi Wibowo (Program Studi Pendidikan Bahasa Arab bekerjasama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan., 2021)
This article was a study of the intersection of philosophy with Arabic. Philosophy is essentially an attempt to understand or understand reality in terms of its meanings and values. Reality is something that symbolizes language. Therefore, language is a vital tool in philosophizing, as a tool to communicate the results of thoughts. The intersection of philosophy with Arabic began in the Umayyad period, preceded by a period of conquest when Arabs took over areas previously under Roman rules, such as Egypt and Syria in the 7th century. The intersection of these Greek thoughts with Arabic occurred when the caliph Abdul Malik bin Marwan carried out Arabization reforms massively. During the Abbasid dynasty, translation activities dominated. The progress of the translation activity was fully supported by the authorities with the establishment of an institution called Bayt al-hikmah. This translation activity was one of the drivers of the rebirth of philosophical studies. We can say that without the contribution of translation in the golden age of Islam, Europe would never have emerged from the dark ages.